Interleukins expression by rat Lymphocytes exposed to chronic intermittent normobaric hypoxia - Calderon-Jofre, Rodrigo; Bernal, Giuliano; Moraga, Daniel; Moraga, Fernando A. (Frontiers in Physiology, 2025)
Acute and chronic hypoxia modulate the expression of inflammatory mediators known as cytokines. However, studies in chronic and intermittent hypobaric or normobaric hypoxia, like those described in miner’s population, are scarce or absent. In this study, we evaluate the effect of chronic intermittent normobaric hypoxia (CINH) on the hematological response and the expression of lymphocyte cytokines IL-1, IL-2, IL-6, and IL-10 in rats. A total of 20 Sprague-Dawley rats were divided into two groups: a) CINH (FiO2 10%, n = 10) and b) Control (normoxic, n = 10). Systolic arterial pressure and heart rate were measured using a tail-cuff sensor. Blood samples were obtained from both groups for hematological studies, and expression of cytokines obtained from lymphocytes was determined by RT-PCR. Hematocrit, hemoglobin, platelet count, and hematological constant were elevated, and leucocyte count decreased in CINH rats. In addition, systolic arterial pressure in CINH rats was significantly increased (over 50%). Cytokine expression from lymphocytes showed that IL-2, and IL-10 increased by 140% and 38%, respectively; IL-6 showed no significant change, while IL-1β expression decreased by 18%. In this regard, CINH could activate an inflammatory response mediated by IL-2. However, this response could be attenuated by increased IL-10 expression, a known anti-inflammatory cytokine, and decreased IL-1β and IL-6 expression, indicative of an adaptation mechanism to CINH.